Análisis de alternativas acerca del manejo de los Residuos de Construcción y Demolición en el ámbito estructural y ambiental (2022)
The increase in the generation of construction waste is notorious. For this reason, this document aims to promote knowledge about CDW, showing the limitations that exist and how to improve these aspects, and thus expand the information panorama about this waste, demonstrating that it is possible to implement it through an organized and collective management